1985
DOI: 10.1007/bf00543332
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of famotidine, a new H2-receptor antagonist, in relation to renal function

Abstract: The pharmacokinetics of a new, potent H2-receptor antagonist, famotidine, 20 mg i.v. was studied in 7 subjects with normal renal function and in 24 patients with varying degrees of renal impairment. The volume of distribution at steady state was 1.141/kg in normal subjects and was not altered in renal failure. The half-life of elimination was 2.59 h in normal subjects and was unchanged in mild renal failure (creatinine clearance, CLCR 90-60 ml/min/1.48 m2) but was increased to 4.72 h in moderate renal failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 6 publications
4
26
1
Order By: Relevance
“…The volume of distribution in dialysis free patients and patients undergoing CHF did not differ significantly from that in subjects with normal kidney function. These findings are in agreement with those of Takabatake et al (1986).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The volume of distribution in dialysis free patients and patients undergoing CHF did not differ significantly from that in subjects with normal kidney function. These findings are in agreement with those of Takabatake et al (1986).…”
Section: Discussionsupporting
confidence: 83%
“…The study of Takabatake et al (1985) on the disposition of famotidine in patients with renal failure revealed that with decreasing creatinine clearance the half-life of famotidine was significantly prolonged. This is supported by our finding in patients with a creatinine clearance less than 5 ml min-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations